Protocol for assessing if behavioural functioning of infants born <29 weeks' gestation is improved by omega-3 long-chain polyunsaturated fatty acids: follow-up of a randomised controlled trial. Issue 5 (5th May 2021) - Gould, Jacqueline F; Roberts, Rachel M; Anderson, Peter J; Makrides, Maria; Sullivan, Thomas R; Gibson, Robert A; McPhee, Andrew J; Doyle, Lex William; Opie, Gillian; Travadi, Javeed; Cheong, Jeanie L Y; Davis, Peter G; et al.
Abstract : Introduction: During the last trimester of pregnancy, the fetal brain undergoes a rapid growth spurt and accumulates essential nutrients including docosahexaenoic acid (DHA). This takes place ex-utero for infants born <29 weeks' gestation, without the in-utero provisions of DHA. Infants born <29 weeks' are more likely to experience behavioural and emotional difficulties than their term-born counterparts. It has been hypothesised that supplementing preterm infants with dietary DHA may alleviate insufficiency and subsequently prevent or minimise behavioural problems. This protocol describes a follow-up of infants born <29 weeks gestation who were enrolled in a randomised controlled trial (RCT) of DHA supplementation. We aim to determine whether DHA supplementation improves the behaviour, and general health of these infants. Methods and analysis: Infants born <29 weeks' gestation were enrolled in a multicentre blinded RCT of enteral DHA supplementation. Infants were randomised to receive an enteral emulsion that provided 60 mg/kg/day of DHA or a control emulsion commenced within the first 3 days of enteral feeding, until 36 weeks' postmenstrual age or discharge home, whichever occurred first. Families of surviving children (excluding those who withdrew from the study) from the Australian sites (up to 955) will be invited to complete a survey. The survey will include questions regarding child behavioural and emotional functioning, executive functioning, respiratory health and general health. We hypothesise that the DHA intervention will have a benefit on the primary outcome, parent-rated behaviour and emotional status as measured using the Total Difficulties score of the Strengths and Difficulties Questionnaire. Detecting a 2-point difference between groups (small effect size of 0.25 SD) with 90% power will require follow-up of 676 participants. Ethics and dissemination: The Women's and Children Health Network Human Research Ethics Committee reviewed and approved the study (HREC/16/WCHN/184). Results will be disseminated in peer-reviewed publications and conference presentations. Trial registration number: ACTRN12612000503820.